2019
DOI: 10.1155/2019/5134360
|View full text |Cite
|
Sign up to set email alerts
|

Impairment on Cardiopulmonary Function after Marathon: Role of Exhaled Nitric Oxide

Abstract: Background. The endurance exercise is capable of inducing skeletal muscle, heart, and respiratory fatigue, evidenced by morphofunctional cardiac changes, release of myocardial injury biomarkers, and reduction of maximal voluntary ventilation and oxygen consumption (VO2) at peak exercise. Purpose. The aim of this study was to investigate whether marathoners present cardiac fatigue after marathon and whether it correlates with pulmonary levels of exhaled nitric oxide (eNO) and pulmonary inflammation. Methods. 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Prolonged exercise is a physiological stress which promotes hyperinflammation following anti-inflammatory compensatory response characterized by the increase on inflammatory mediators such as IL-6, IL-8, IL-ra, IL-10, and C-reactive protein (CRP) [15]. The exacerbated inflammation contributes to transient immunosuppression, as well as hematological and cardiopulmonary changes, and muscle and renal damage induced by exercise [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged exercise is a physiological stress which promotes hyperinflammation following anti-inflammatory compensatory response characterized by the increase on inflammatory mediators such as IL-6, IL-8, IL-ra, IL-10, and C-reactive protein (CRP) [15]. The exacerbated inflammation contributes to transient immunosuppression, as well as hematological and cardiopulmonary changes, and muscle and renal damage induced by exercise [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…NO can be measured noninvasively in the exhaled air by chemiluminescence, by using bench [16] or portable [12] NO detecting devices. In fact, increased levels of NO have been associated not only with several aspects of asthma [6,7,8,9], but also with exercise-induced bronchoconstriction, which is a highly prevalent characteristic of asthmatic patients [16,17]. In the present study, it was found that asthmatic children presented high levels of exhaled NO, ranging among 25-30 ppb, which clearly indicates an inflammatory process of the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Beside Th2 mediators and growth factors, nitric oxide (NO), has also been linked to asthma development, severity and exacerbations [6,7,8,9].NO is aninstable gas, considered a highly reactive nitrogen specie, which present a very short half-life.NO can be measured noninvasively in the exhaled air by chemiluminescence, by using bench [16]or portable [12]NO detecting devices.In fact, increased levels of NO have been associated not only with several aspects of asthma [6,7,8,9], but also with exercise-induced bronchoconstriction, which is a highly prevalent characteristic of asthmatic patients [16,17]. In the present study, it was found that asthmatic children presented high levels of exhaled NO, ranging among 25-30ppb, which clearly indicates an inflammatory process of the airways.…”
Section: Discussionmentioning
confidence: 99%